The Relationship Between Corporate Social Responsibility Practices and Firm Performance of Domestic Banks in Malaysia. - Santhirasegar, Janartini; Ramakrishnan, Suresh; S Hishan, Sanil; Mohd Jamal, Noriza (International Journal of Engineering and Technology, 2018)
The focus on corporate social responsibility (CSR) has been active in the public attention within Malaysia for the past ten years, and as such has become a strength in many corporationsâ€™ public relations as what demonstrate in the bank's campaign strategy. In fact, the importance of CSR initiatives may have a direct impact on the success of the business as many organizations worldwide have come under pressure to meet the terms of the international CSR standards and practices. Therefore, this study seeks to measure the level of CSR disclosure by domestic banks in Malaysia from the year 2008 until 2015. This study used content analysis method to identify the CSR activities and disclosure score that was obtained from annual reports and sustainability reports for the commercial banks. Overall, the findings indicate that commercial banks in Malaysia promotes important roles in community and philanthropy. Additionally, this study will also examine the relationship between CSR and firm performance of in commercial banks Malaysia from the year 2008 until 2015. This study used correlation analysis to analyze the relationship between dependent variables, namely return on assets, return on equity and earnings per share, and independent variables which is the CSR disclosure. The overall sample results revealed only return on asset and return on equity has significant relationship with CSR. Thus, a greater profitability can be achieved through appropriate CSR practice. CSR reporting should not be a practice only for special or infrequent events rather it should be a continuous process, and banks need to incorporate CSR reporting more.Â Â Â